ASPECTS OF THE CONSISENCY OF ISLAMIC BOORDING SCHOOL EDUCATION IN IMPROVING STUDENT DICIPLINE - saputra, aji rajab; Wahyu, Wahyu; Anis, M. Z Arifin (Universitas Lambung Mangkurat, 2023)
Nowadays, pesantren as an educational and da'wah entity is faced with various challenges, one of which is the challenge of fostering and educating students to have a disciplined attitude. A pesantren that has a lot of santri must know very well about the methods and ways to shape their character. One of them is educating characters so that they are able to be disciplined in everything, both in terms of worship, school, muamalah and their daily lives in the dormitory. So that this method can be accepted by every student, the role of Islamic boarding school education in improving the disciplined character education of the students is an obligation. In applying the character of the santri, appropriate steps are needed to match the educational goals of the pesantren. One of the most basic characters that must be instilled in the student's personality is the character of discipline. The character of discipline affects all aspects of santri behavior in everyday life. By having a disciplined character, students will show other traits such as responsibility, punctuality and good time management in memorizing the Qur'an.